Sublethal effects of wild-type and a vIF-2α-knockout Frog virus 3 on postmetamorphic wood frogs (Rana sylvatica): potential for a stage-specific reservoir - Joe-Felix Bienentreu; Leon Grayfer; Danna M. Schock; Matthew Guerreiro; Melanie Mehes-Smith; Stephanie J. DeWitte-Orr; Jacques Robert; Craig R. Brunetti; David Lesbarrères (Canadian Science Publishing, 2020)
Ranaviruses have been associated with rising numbers of mass die-offs in amphibian populations around the globe. However, most studies on ranaviruses to date focused on larval amphibians. To assess the role of postmetamorphic amphibians in the epidemiology of ranaviruses and to determine the role of viral immune-suppression genes, we performed a bath-exposure study on post-metamorphic wood frogs (Rana sylvatica) using environmentally relevant concentrations of wild-type Frog virus 3 (WT FV3), and a gene-knockout mutant (KO FV3), deficient for the putative immune-suppression gene vIF-2α. We observed a 42% infection rate and 5% mortality across the virus challenges, with infection rates and viral loads following a dose-dependent pattern. Individuals exposed to the knockout variant exhibited significantly decreased growth and increased lethargy compared with wild-type treatments. Although 85% of exposed individuals exhibited common signs of ranavirosis throughout the experiment, most of these individuals did not exhibit signs of infection by 40 d post-exposure. Overall, we showed that even a single short time exposure to environmentally relevant concentrations of ranavirus may cause sublethal infections in postmetamorphic amphibians, highlighting the importance of this life stage in the epidemiology of ranaviruses. Our study also supports the importance of the vIF-2α gene in immune-suppression in infected individuals.